2013
DOI: 10.1097/qad.0b013e328361a427
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of B-cell functions during HIV-1 infection

Abstract: A variety of B-cell dysfunctions are manifested during HIV-1 infection, as reported early during the HIV-1 epidemic. It is not unusual that the pathogenic mechanisms presented to elucidate impairment of B-cell responses during HIV-1 infection focus on the impact of reduced T-cell numbers and functions, and lack of germinal center formation in lymphoid tissues. To our understanding, however, perturbation of B-cell phenotype and function during HIV-1 infection may begin at several different B-cell developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
1
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 103 publications
(133 reference statements)
4
78
1
1
Order By: Relevance
“…The dysregulation of the B cell compartment in HIV infection is likely caused by both direct immune stimulation and bystander mechanisms of immunologic damage (14); some of which persist in the presence of ART (15). A recent study reported that bulk, non-antigen-specific RM B cells in peripheral blood are depleted during HIV infection, while AM and TLM cell frequencies expand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dysregulation of the B cell compartment in HIV infection is likely caused by both direct immune stimulation and bystander mechanisms of immunologic damage (14); some of which persist in the presence of ART (15). A recent study reported that bulk, non-antigen-specific RM B cells in peripheral blood are depleted during HIV infection, while AM and TLM cell frequencies expand.…”
Section: Discussionmentioning
confidence: 99%
“…As Tfh cell expansion has been associated with a concurrent expansion of B cells and plasma cells in lymphoid germinal centers, we next studied bulk and HIV-specific B cell phenotypes in the peripheral blood of the cohorts to determine how the observed To analyze the effects of antigenemia on memory B cell subsets, bulk B cells were separated into the four following memory subsets based on expression of CD21 and CD27 as previously described (14,15,17): CD27 ϩ CD21 Ϫ activated memory (AM), CD27 ϩ CD21 ϩ resting memory (RM), CD27 Ϫ CD21 Ϫ tissue-like memory (TLM), and CD27 Ϫ CD21 ϩ intermediate memory (IM). We found that peripheral blood mononuclear cells (PBMCs) from HIV-infected individuals have altered profiles of B cell memory subtypes compared to those from uninfected individuals.…”
Section: Bulk B Cells Are Expanded In Uncontrolled Hiv Infection But mentioning
confidence: 99%
See 1 more Smart Citation
“…Although HIV does not productively infect B cells, numerous phenotypic and functional abnormalities of B cells have been described in HIV disease (21,22). The indirect and persistent effects of ongoing HIV replication have been associated with aberrant B cell activation, increased B cell exhaustion, as well as deficiencies in the development of normal B cell memory (21).…”
Section: Introductionmentioning
confidence: 99%
“…The indirect and persistent effects of ongoing HIV replication have been associated with aberrant B cell activation, increased B cell exhaustion, as well as deficiencies in the development of normal B cell memory (21). Whereas resting memory B cells represent the predominant memory subset in healthy individuals, their frequencies are reduced in almost all stages of HIV disease, regardless of treatment status (21,22). In untreated HIV-viremic individuals, tissue-like and activated memory B cells are the predominant memory subsets, the former being associated with HIV-induced cellular exhaustion and the latter, apoptosis (21).…”
Section: Introductionmentioning
confidence: 99%